REVENUE MODEL DAN CONDITIONAL REVENUE MODEL UNTUK MENDETEKSI MANAJEMEN LABA - Heni Yusnita (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
Earnings management is a management action to manage the profitability of a company. The purpose of this study is to indicate the accrual earning management using revenue model and conditional revenue model. This study adopts the research conducted by Stubben (2010) where there are two measurement models to detect the presence of accrual earnings management. Object of this research is the companies listed in Indonesia Stock Exchange. The technique of data analysis is descriptive statistics to determine the residual value in each companies. These results prove that the revenue model is able to indicate the companies 34 of the total 38 in the manufacturing companies indicated accrual earnings management. Conditional revenue model is able to indicate the companies 36 of the total 38 in the manufacturing companies indicated accrual earnings management.